Invasion biology of Aedes japonicus japonicus (Diptera: Culicidae) - Kaufman, Michael G; Fonseca, Dina M (Annual review of entomology, 2014)
Aedes japonicus japonicus (Theobald) (Diptera: Culicidae) has recently expanded beyond its native range of Japan and Korea into large parts of North America and Central Europe. Population genetic studies begun immediately after the species was detected in North America revealed genetically distinct introductions that subsequently merged, likely contributing to the successful expansion. Interactions, particularly in the larval stage, with other known disease vectors give this invasive subspecies the potential to influence local disease dynamics. Its successful invasion likely does not involve superior direct competitive abilities, but it is associated with the use of diverse larval habitats and a cold tolerance that allows an expanded seasonal activity range in temperate climates. We predict a continued but slower expansion of Ae. j. japonicus in North America and a continued rapid expansion into other areas as this mosquito will eventually be considered a permanent resident of much of North America, Europe, Asia, and parts of Hawaii.